Satisfaction of Attendants to a Family Medicine Training Center and a Primary Health Care Center in Baghdad - Al-Jumaily, Meha; Al-Lami, Faris H. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: In Iraq, Primary Health Care (PHC) services are provided trough a network of about 1900 PHC Centers (PHCC). Recently, attempts were made to enhance the practice of primary health care to encompass the family health model. Expressed attendants' satisfaction and opinion about provided care at any health care setting is an important predictor of utilization and continuity of obtaining care from the same source. The objective: is to describe and compare satisfaction of attendants of a Family Medicine Training Center (FMTC) and a PHCC in Baghdad.Subjects and Methods: a comparative cross sectional study conducted on a random sample of 300 attendants from each center. Attendants’ satisfaction towards the center’s building; doctor's approach, provided medical services and attendants’ continuity manner were studied.Results: About 53% of FMTC attendants and 40% of PHCC attendants stated a very good building's location. Around 7.3% of PHCC attendants, and 3.7% of FMTC attendants considered hygienic standard as "poor", (P=0.05). Doctor reception was considered as “poor” in 2.7% of FMTC attendants compared to 0% for the PHCC, (P=0.000). Around 16% of FMTC attendants considered the time spent by the doctor as "inadequate" compared to 4.7% of PHCC attendants, (P=0.000). Around 48% of PHCC attendants were given appointment for follow up, compared to 19% of FMC attendants (P=0.000). About 58% reported availability of investigations and drugs in FMTC compared to 40.3% for PHCC attendants,  (P=0.000).Conclusion: FMTC attendants are more satisfied to building's related variables and availability of medical services but less satisfied by doctor's approach with less intention to continue attending the center.